Analysis of a case series of behavioral variant frontotemporal dementia: Emphasis on diagnostic delay - Henrique Cerqueira Guimarães; Thiago Cardoso Vale; Victor Pimentel; Nayara Carvalho de Sá; Rogério Gomes Beato; Paulo Caramelli (Dementia & Neuropsychologia)
ABSTRACT Introduction: Despite many advances in the characterization of the behavioral variant of frontotemporal dementia (bvFTD), the diagnosis of this syndrome poses a significant challenge, while delays or diagnostic mistakes may impact the proper clinical management of these patients. Objective: To describe the clinical profile at first evaluation of a sample of patients with bvFTD from a specialized outpatient neurological unit, with emphasis on the analysis of the delay between the onset of symptoms and diagnosis. Methods: We selected 31 patients that fulfilled international consensus criteria for possible or probable bvFTD. Patients' medical admission sheets were thoroughly reviewed. Results: Patients' mean age was 67.9±8.2 years; 16 (51.6%) were men. Mean number of years of formal education was 7.7±4.0 years. Mean age at onset was 62.2±7.7 years, indicating a mean of 5.8 years of diagnostic delay. Thirteen patients (41.9%) presented with initial behavioral complaints only, eleven patients (35.5%) had mixed behavioral and memory complaints, five patients (16.1%) presented with memory complaints only, and two patient (6.4%) had behavioral and speech problems. Nine patients (29%) were admitted with alternative diagnoses. Mean and standard deviation scores for the mini-mental state examination, animal category fluency and memory test for drawings (five-minute delayed recall) were 19.3±6.3, 8.3±4.1 and 3.7±2.7, respectively. Conclusion: Most patients from this sample were evaluated almost six years after the onset of symptoms and performed poorly on both cognitive screening tests and functional evaluation measures.